People media [videorecording] - Del Mundo, Clodualdo; Del Mundo, Herky
Gives an overview of the various media processes in the country. Highly visual and purposely abstract in its approach, it creates the right mood and asks the question for whom should media ben It is a third prize winner at the 1982 ECP short Film Festival.